1989
DOI: 10.1079/bjn19890045
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of the dental properties of soft drinks

Abstract: The composition and dental properties of eight different soft drinks, representing some of the most popular types used in the UK, were examined. Demineralization experiments were conducted on hydroxylapatite, the basic component of dental enamel, determining calcium dissolving by atomic absorption spectroscopy and phosphorus by u.v. visual spectrophotometry. The titratable acid content of the drinks was found to give a better guide than their pH to their potential dental erosiveness. The sugar content, in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 11 publications
4
54
0
3
Order By: Relevance
“…In the present study, it was found that, in general, fruity teas had higher erosive potential than natural ones, which is in agreement with the literature [22]. In a systematic review that included a number of epidemiological, cutoff, laboratory, and case-control studies published between 2000 and 2012 with human and animal specimens, it was found that fruity green and black teas, with added herbs and sugar, had high erosive potential [23], corroborating the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was found that, in general, fruity teas had higher erosive potential than natural ones, which is in agreement with the literature [22]. In a systematic review that included a number of epidemiological, cutoff, laboratory, and case-control studies published between 2000 and 2012 with human and animal specimens, it was found that fruity green and black teas, with added herbs and sugar, had high erosive potential [23], corroborating the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…The inherent acidity of these drinks is mainly due to the addition of acids during their manufacturing process to improve their organoleptic properties since acidity is a key factor to stimulate taste and counteract sweetness. been highlighted as having a particularly detrimental effect on dental enamel and can cause severe demineralisation due to its ability to chelate minerals of apatite such as calcium 20,21 , while malic acid, present in the diet cola drinks produced by ASDA, Co-op and Marks & Spencer, is slightly less detrimental 22 . In a study by Edwards and co-workers, 23 the higher TA for fruit juices compared with other carbonated drinks was reported to be due to citric acids derived from the fruit.…”
Section: Discussionmentioning
confidence: 99%
“…While TA is responsible for maintaining the H + concentration available for the interaction with the tooth surface 10,22 , its importance in the clinically erosive situation is influenced by conditions such as exposure time and the ratio of the volume of eroding solution to the area of exposed tooth surface 18 . The in vitro conditions in which the drinks were tested in this study will impact on the clinical relevance of the results since biological factors such as salivary flow rate and its buffering capacity, as well as individual's drinking habits, are important modifiers in the erosion process clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determination of dental enamel dissolution by assessing the amount of calcium or phosphate dissolved from the apatite crystals of dental hard tissue could also be regarded as a possible tool for assessing dental erosions. Hence, some authors had applied calcium determina-tion in erosive, acidic solutions after prolonged contact (range 2 min to 24 h) of the solutions with dental hard tissue using calcium sensitive electrodes, atomic adsorption spectrophotometer or the highly sensitive method of inductively coupled plasma mass spectrometry [68][69][70][71][72] Calcium-sensitive electrodes often need a specific pH of the environment to work precisely. Additionally, cal-cium complexes formed with certain acids (e.g.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%